The Effect Of Workload, Organizational Culture And Communication On Organizational Citizenship Behavior With Organizational Commitment As An Intervening Variable At Pt. Daihatsu Capella Medan - Febry Rizky Al Fadilla Sitompul; Sri Rahayu (International Forum of Researchers and Lecturers, 2024)
The purpose of the study was to determine the direct and indirect effects of workload variables, organizational culture, communication on organizational citizenship behavior through organizational commitment in employees of PT Daihatsu Capella Medan. This type of research is causal associative and uses quantitative research methods. The population in this study were all employees at PT Capella Medan Daihatsu totaling 78 people. The sample withdrawal method uses nonprobability sampling method with census sampling technique. So the sample in this study amounted to 78 employees at PT Capella Medan Daihatsu. The results of the study are workload directly has a significant effect on organizational commitment of PT Capella Medan Daihatsu, organizational culture directly has a significant effect on organizational commitment of PT Capella Medan Daihatsu, communication directly has a significant effect on organizational commitment of PT Capella Medan Daihatsu, workload directly has a significant effect on organizational citizenship behavior of PT Capella Medan Daihatsu, work culture directly has a significant effect on organizational citizenship behavior of PT Capella Medan Daihatsu, communication directly has a significant effect on organizational citizenship behavior of PT Capella Medan Daihatsu. Capella Medan Daihatsu, organizational commitment directly has a significant effect on organizational citizenship behavior of PT. Capella Medan Daihatsu, workload indirectly has a significant effect on organizational citizenship behavior through organizational commitment at PT. Capella Medan Daihatsu, organizational culture indirectly has a significant effect on organizational citizenship behavior through organizational commitment at PT. Capella Medan Daihatsu, communication indirectly has a significant effect on organizational citizenship behavior through organizational commitment at PT. Capella Medan Daihatsu.